Basic Image Analysis for the Measurement of Mineral Liberation - R. P. King (The Minerals, Metals and Materials Society, 1995)
The essential features of an image analysis system for the measurement of mineral liberation are described. Good procedures for image acquisition and image processing prior to image analysis are defined. The basic stereological methods for the measurement of volume fraction, surface area per unit volume, particle size distribution and liberation spectra are given. The appropriate methods for fractal correction when measuring perimeters of irregular features and for frame correction when measuring linear intercepts are developed. Practically useful and accurate procedures for the stereological correction of particle size and liberation distribution methods are given.